Inertial Subrange Optimization in Eddy Dissipation Rate Estimation and Aircraft-Dependent Bumpiness Estimation - Zhenxing Gao; Qilin Zhang; Kai Qi (Aerospace)
Atmospheric turbulence leads to aircraft bumpiness. In current vertical wind-based eddy dissipation rate (EDR) estimation algorithms based on flight data, the inertial subrange is determined empirically. In application, specific aircraft bumpiness can only be described by an EDR indicator. In this study, the objective turbulence severity and aircraft-related bumpiness estimation were explored with an optimized inertial subrange. To obtain the inertial subrange, the minimum series length to estimate EDR was determined under different flight data sampling rate. In addition, the basic series length to estimate the inertial subrange was determined according to Blackman–Tukey spectra estimation theory. In aircraft-dependent bumpiness estimation, the unsteady vortex lattice method (UVLM) was designed to obtain an accurate aircraft acceleration response to turbulence. An in situ aircraft bumpiness estimation and bumpiness prediction method were further proposed. Simulation and experiments on real flight data testified the optimized aircraft-independent EDR estimation and aircraft-dependent bumpiness estimation successively. This study can be further applied to estimate the turbulence severity on a particular airway, while the bumpiness of specific aircraft can be predicted.